Fungrim home page

Fungrim entry: 30652c

(n)k=(n+k1)!(n1)!\left(n\right)_{k} = \frac{\left(n + k - 1\right)!}{\left(n - 1\right)!}
Assumptions:nZ1  and  kZ0n \in \mathbb{Z}_{\ge 1} \;\mathbin{\operatorname{and}}\; k \in \mathbb{Z}_{\ge 0}
\left(n\right)_{k} = \frac{\left(n + k - 1\right)!}{\left(n - 1\right)!}

n \in \mathbb{Z}_{\ge 1} \;\mathbin{\operatorname{and}}\; k \in \mathbb{Z}_{\ge 0}
Fungrim symbol Notation Short description
RisingFactorial(z)k\left(z\right)_{k} Rising factorial
Factorialn!n ! Factorial
ZZGreaterEqualZn\mathbb{Z}_{\ge n} Integers greater than or equal to n
Source code for this entry:
    Formula(Equal(RisingFactorial(n, k), Div(Factorial(Sub(Add(n, k), 1)), Factorial(Sub(n, 1))))),
    Variables(n, k),
    Assumptions(And(Element(n, ZZGreaterEqual(1)), Element(k, ZZGreaterEqual(0)))))

Topics using this entry

Copyright (C) Fredrik Johansson and contributors. Fungrim is provided under the MIT license. The source code is on GitHub.

2021-03-15 19:12:00.328586 UTC